Efeito do nível de estabilização do desempenho na adaptação às perturbações imprevisíveis em tarefas de características de controle distintas - Suziane Peixoto dos Santos Naves (2015)
This study aimed to investigate the effect of stabilization performance level on adaptation to unpredictable perturbations in tasks with different control characteristics. Two experiments were conducted, one with a force control task and another with interception to a moving target. A sample of experiment one consisted of 29 subjects (M = 24.2, SD = 3.4 years), and the task required controlling isometrically 40% of the maximum strength of the flexor muscles of the elbow for three seconds. The experiment consisted of pre-exposure and exposure phase. During pre-exposure, two performance stabilization levels were manipulated: stabilization (SG) and superstabilization (SSG). The SG practiced until reach a block of five trials in a row controlling 40% of maximum strength with error (RMSE) equal or less than 5% during three seconds; SSG practiced until reach the same criterion for six blocks. On the second phase it was inserted perturbations (P1 increment and P2 reduction) of maximal force on a pseudorandom order, interspersed with control trials. The measures used were; RMSE, time to peak force (ms) and number of corrections. The results showed that the superstabilization group adapted better to the perturbations in relation to the stabilization group and combined more efficiently the feedforward and feedback mechanisms for changes. On experiment two the sample consisted of 28 subjects (M = 23.8, SD = 3.7 years) and the task required intercepting a moving target. The experiment had the same design than experiment 1, but the SG performance criterion consisted of intercept the target four trials in a row and SSG six blocks of the same criterion. On exposure phase perturbations were included related to changes in speed (P1 or P2 increase - reduction) target velocity after the movement on set. The performance measures adopted were time absolute error (ms), time constant error (ms), number of attempts by each group in the pre-exposure, time to peak velocity (ms) and number of corrections of movements. The results showed that the superstabilization group adapted better to perturbations than stabilization group and used more efficiently the feedback mechanisms for changes. Summarizing it is possible to conclude that superstabilization conducted to better performance when facing unpredictable perturbations, but with specificities on control mechanisms. At last, adaptation required change on macrostructure of the action program.